Taxonomic novelties in Chamaecrista (Leguminosae: Caesalpinioideae) from Brazil - Rando, Juliana G.; Loeuille, Benoit; Pirani, José Rubens (Phytotaxa, 2013)
In the light of taxonomic studies of Chamaecrista sect. Chamaecrista ser. Coriaceae the status of several varieties is re-evaluated: Three former varieties are recognized at the specific level, two new combinations and one synonymization are here proposed. The geographic distribution and taxonomic affinities of these species are discussed.